SPIRITUAL AND MORAL EDUCATION OF YOUNGER PUPILS (Conference Zone, 2021)
This article discusses the issues of the process of spiritual and moral education of younger students, the pedagogical conditions of work in this area. The main goals, objectives, requirements and planned results of the spiritual and moral education and socialization of the personality of younger students are revealed.